Mindfulness Advancement Questionnaire (Polish adaptation and validation) - Radoń, Stanisław (Studia Psychologica: Theoria et praxis, 2020)
This paper aimed to adaptation of the MINDSENS questionnaire used to measure of advancement in mindfulness among meditators and nonmeditators. The research sample consisted of two groups of people: 1) with meditation experience (N = 656: 74.6% including Christian meditation – 33.5%; mindfulness – 24.4%; concentration techniques such as yoga and transcendental meditation – 16.2%), and 2) without meditation experience (N = 226: 25.4%) controlled for length and frequency of meditation practice and disorders. The validation procedure showed that the Polish adaptation of MINDSENS i.e., the Mindfulness Advancement Questionnaire (Observing, Non-Reactivity, and Decentration) demonstrated the solid factor structure (3-factor model with bifactor), high factor loadings, good composite (0.74 ≤ CR ≤ 0.93) and construct reliability (0.82 ≤ H ≤ 0.93), fine absolute stability (0.76 ≤ rtt ≤ 0.82), and solid external validity. Thus, the validated questionnaire can be used as valuable measure of mindfulness advancement in meditators, clinical and nonclinical populations, aged 15–72.